2022
DOI: 10.3390/pharmaceutics14020219
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Electrospun Nerve Guidance Conduits for Engineering Neural Regeneration

Abstract: Injuries to the peripheral nervous system result in devastating consequences with loss of motor and sensory function and lifelong impairments. Current treatments have largely relied on surgical procedures, including nerve autografts to repair damaged nerves. Despite improvements to the surgical procedures over the years, the clinical success of nerve autografts is limited by fundamental issues, such as low functionality and mismatching between the damaged and donor nerves. While peripheral nerves can regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 93 publications
(163 reference statements)
1
33
0
Order By: Relevance
“…This allows the fibers to be transferred to any target substrates, regardless of their material, and also, potentially, to form bundles from individual fibers suitable for filling hollow nerve guidance conduits used for nerve regeneration. A similar design utilizing bundles of micron fibers inside a polymer tube has already been successfully applied for peripheral nerve regeneration in vivo [13]. Photothermal scaffolds made of fibrous materials were previously fabricated by electrospinning with the addition of light-converting particles to the polymer solution.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This allows the fibers to be transferred to any target substrates, regardless of their material, and also, potentially, to form bundles from individual fibers suitable for filling hollow nerve guidance conduits used for nerve regeneration. A similar design utilizing bundles of micron fibers inside a polymer tube has already been successfully applied for peripheral nerve regeneration in vivo [13]. Photothermal scaffolds made of fibrous materials were previously fabricated by electrospinning with the addition of light-converting particles to the polymer solution.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported preparation and successful application of artificial nerve conduits based on electrospun fibrous materials in biological test systems [13,62,63]. However, relatively few works are deploying fiber nanomaterials with fiber diameters of 100 nm due to technical difficulties of manufacturing [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, PLLA can be easily blended with other materials or bioactive polymers to optimize its surface bioactivity ( Jahromi et al, 2020 ; Siriwardane et al, 2021 ). Furthermore, PLLA-based materials can be fabricated into two-dimensional or three-dimensional (3D) scaffolds with stable nanofibrous and porous topology which provide the biomimetic structures for nerve cell adhesion and growth while supporting neural tissue formation ( Almansoori et al, 2020 ; Behtaj et al, 2022 ; Weir et al, 2022 ). Moreover, PLLA-based scaffolds have the potential to be combined with various therapeutic approaches such as drug delivery, electrical stimulation, magnetic stimulation, and stem cell therapy, which have been explored in nerve repair and regeneration ( Zhang et al, 2017 ; Chen et al, 2020 ; Jedari et al, 2020 ; Rahimi-Sherbaf et al, 2020 ; Tonellato et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…St. John et al, in their review entitled “Advances in Electrospun Nerve Guidance Conduits for Engineering Neural Regeneration”, reported the capability of the electrospun approach to fabricate fibers of various scales and which have a large surface area with a three-dimensional porous structure resembling the native extracellular matrix for regeneration of the nervous system [ 21 ]. Considerations regarding conditions of the injury, as well as the requirements and structure for the nerve guidance conduits, were also discussed.…”
mentioning
confidence: 99%